2D Materials: Strain Engineering of 2D Materials: Issues and Opportunities at the Interface (Adv. Mater. 45/2019). Issue 45 (6th November 2019) - Dai, Zhaohe; Liu, Luqi; Zhang, Zhong
Abstract : The strain engineering of 2D materials is exciting, because an individual sheet can survive remarkably large mechanical strain and its atomic thinness allows out‐of‐plane deformation, like a piece of paper. These exceptional circumstances create opportunities for the study of new fundamental physics and applications of 2D materials emerging at a large strain level, and are discussed by Luqi Liu, Zhong Zhang, and Zhaohe Dai in article number 1805417 .